Dietary berberine alleviates high carbohydrate diet-induced intestinal damages and improves lipid metabolism in largemouth bass (Micropterus salmoides) - Gong, Yulong; Lu, Qisheng; Liu, Yulong; Xi, Longwei; Zhang, Zhimin; Liu, Haokun; Jin, Junyan; Yang, Yunxia; Zhu, Xiaoming; Xie, Shouqi; Han, Dong (Frontiers in Nutrition, 2022)
High carbohydrate diet (HCD) causes metabolism disorder and intestinal damages in aquaculture fish. Berberine has been applied to improve obesity, diabetes and NAFLD. However, whether berberine contributes to the alleviation of HCD-induced intestinal damages in aquaculture fish is still unclear. Here we investigated the effects and mechanism of berberine on HCD-induced intestinal damages in largemouth bass (Micropterus salmoides). We found dietary berberine (50 mg/kg) improved the physical indexes (VSI and HSI) without affecting the growth performance and survival rate of largemouth bass. Importantly, the results showed that dietary berberine reduced the HCD-induced tissue damages and repaired the barrier in the intestine of largemouth bass. We observed dietary berberine significantly suppressed HCD-induced intestinal apoptosis rate (from 31.21% to 8.35%) and the activity level of Caspase3/9 (P < 0.05) by alleviating the inflammation (il1β, il8, tgfβ and IL-6, P < 0.05) and ER stress (atf6, xbp1, perk, eif2α, chopa, chopb and BIP, P < 0.05) in largemouth bass. Further results showed that dietary berberine declined the HCD-induced excessive lipogenesis (oil red O area, TG content, acaca, fasn, scd, pparγ and srebp1, P < 0.05) and promoted the lipolysis (hsl, lpl, cpt1a and cpt2, P < 0.05) via activating adenosine monophosphate-activated protein kinase (AMPK, P < 0.05) and inhibiting sterol regulatory element-binding protein 1 (SREBP1, P < 0.05) in the intestine of largemouth bass. Besides, we also found that dietary berberine significantly promoted the hepatic lipid catabolism (hsl, lpl, cpt1a and cpt2, P < 0.05) and glycolysis (pk and ira, P < 0.05) to reduce the systematic lipid deposition in largemouth bass fed with HCD. Therefore, we elucidated that 50 mg/kg dietary berberine alleviated HCD-induced intestinal damages and improved AMPK/SREBP1-mediated lipid metabolism in largemouth bass, and evaluated the feasibility for berberine as an aquafeed additive to enhance the intestinal function of aquaculture species.